Optimum allocation unit catching small pelagic fish in the water in Kei Island Southeast Maluku - J. Tahapary; Bruri B. Tumiwa (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Small pelagic fish is one of the fish are potential resources and high compared to other kinds of fish in Kei Island Southeast Maluku. The aim of this research is to determine the optimum allocation unit arrest in the utilization of small pelagic fish in the Kei Island waters. An instrument grap used for catching small pelagic fish in the waters Kei Island is a lift net, purse seine, drift gill net and encircling gill net. A method of collecting data covering data resources fish, fuel, perational cost labor, the number of units arrest, and tracing of references pertaining to an object research. Analysis of data using linear goal programming ( LGP ) to provide information is important in allocating a unit of catching small pelagic fishoptimally, and that is how allocation grap, optimal an instrument used how big achievement the purpose of which is willed according to the target, and just how much resources be used in achieving its goal. A kind of small pelagic fish widely distributed in Kei Island waters is Decapterus sp., Rastrelliger sp., Selaroides spp., Sardinela sp., Clupea s.p and Stolephorus sp. The result of this research is optimum allocation unit catching small pelagic fish in the Kei Island waters for the implementation of allocation technology usually in the utilization of resources fish